2020
DOI: 10.1002/art.41308
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Intravoxel Incoherent Motion Diffusion‐Weighted Magnetic Resonance Imaging With T1 Mapping to Assess Myocardial Perfusion and Fibrosis in Systemic Sclerosis: Association With Cardiac Events From a Prospective Cohort Study

Abstract: Objective Myocardial involvement may occur during systemic sclerosis (SSc) and can lead to impaired myocardial contraction and/or arrhythmia. Cardiac magnetic resonance imaging (MRI) is used for noninvasive characterization of the myocardium. The aim of this study was to evaluate the utility of cardiac MRI with intravoxel incoherent motion (IVIM) diffusion‐weighted imaging (DWI) and longitudinal relaxation time (T1) sequence mapping for assessment of myocardial microvascular and interstitium impairment in SSc.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 28 publications
1
25
0
1
Order By: Relevance
“…It is increasingly appreciated that there is a significant burden of myocardial fibrosis in SSc that is not manifest by either diastolic or systolic cardiac dysfunction [15,48,49]. CMR measures of both focal and diffuse myocardial fibrosis have been shown to predict the development of heart failure and arrhythmia, and a large burden of fibrosis is associated with increased mortality [14,15,50]. The prevalence of myocardial fibrosis is much greater than that of systolic dysfunction and reduced LVEF in SSc, despite the observed link between fibrosis and impaired cardiac function [50].…”
Section: Impaired Cardiac Function and Heart Failurementioning
confidence: 99%
See 2 more Smart Citations
“…It is increasingly appreciated that there is a significant burden of myocardial fibrosis in SSc that is not manifest by either diastolic or systolic cardiac dysfunction [15,48,49]. CMR measures of both focal and diffuse myocardial fibrosis have been shown to predict the development of heart failure and arrhythmia, and a large burden of fibrosis is associated with increased mortality [14,15,50]. The prevalence of myocardial fibrosis is much greater than that of systolic dysfunction and reduced LVEF in SSc, despite the observed link between fibrosis and impaired cardiac function [50].…”
Section: Impaired Cardiac Function and Heart Failurementioning
confidence: 99%
“…The risk of death from SSc, and in particular heart disease in SSc, has remained largely unchanged for over 40 years [5]. This includes the risk of sudden cardiac death (SCD) which is reported to occur in up to 9% of individuals with SSc, [8][9][10][11][12][13][14][15] increasing to 67% in patients with clinically overt SHI [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 34 36 The Scleroderma Arrhythmia Clinical Utility Study included 150 patients with SSc and reported predictive value of increased T2 ratio, a marker of myocardial oedema and LGE% for the development of ventricular rhythm disturbances and sudden cardiac death in SSc. Another study in 40 consecutive patients with SSc that had T1 mapping and diffusion-weighted imaging CMR showed association of T1 native with the occurrence of CV events 37 while Bordonaro et al , looking retrospectively at a symptomatic SSc cohort reported LGE, T1 native and ECV as independent predictors of CV events. 38 These studies included patients with both primary and secondary CVD, capturing real-life cohorts.…”
Section: Discussionmentioning
confidence: 96%
“…Multiparametric imaging derived from CMR has been increasingly used to evaluate a variety of cardiac diseases including ischemic cardiomyopathy and non-ischemic cardiomyopathy resulting from diabetes mellitus, amyloidosis, and hypertension [12][13][14]. However, to the best of our knowledge, few studies have simultaneously evaluated myocardial strain, microcirculation perfusion and myocardial fibrosis in patients with CTD [15,16]. Therefore, the present study aimed to quantitatively assess the multiple parameters derived from CMR including LV global myocardial deformation, microvascular perfusion, and late gadolinium enhancement (LGE) in CTD patients and investigated the association between LV deformation and myocardial perfusion, as well as LGE.…”
Section: Introductionmentioning
confidence: 99%